Effect of Fashion Subscription Services on Consumer Retention in Japan - Shimizu, Ayaka (International Journal of Fashion and Design, 2024)
Purpose: The aim of the study was to analyze the effect of fashion subscription services on consumer retention in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Fashion subscription services in Japan significantly boost consumer retention, with 70% of users staying subscribed due to personalized styling and convenience. The tailored fashion choices and elimination of shopping hassles increase user satisfaction. Additionally, 60% of respondents are likely to recommend the service, enhancing word-of-mouth potential. Unique Contribution to Theory, Practice and Policy: Customer loyalty theory, expectation-confirmation theory (ECT) & self-determination theory (SDT) may be used to anchor future studies on fashion subscription services on consumer retention in Japan. Practitioners should focus on refining the algorithms that drive personalization in fashion subscription services. Policymakers should ensure that regulations are in place to protect consumers from unfair practices in fashion subscription services. Keywords: Fashion Subscription Services, Consumer Retention